Polyethylenimine-cross-linked cellulose nanocrystals for highly efficient recovery of rare earth elements from water and a mechanism study. Issue 20 (12th September 2017) - Zhao, Feiping; Repo, Eveliina; Song, Yang; Yin, Dulin; Hammouda, Samia Ben; Chen, Li; Kalliola, Simo; Tang, Juntao; Tam, Kam C.; Sillanpää, Mika
Abstract : PEI acts not only as a cross-linker but also as a chelating agent for RE ions. Abstract : The ever-increasing demand for Rare Earth Elements (REEs) due to their increased use in various high-tech and futuristic applications has stimulated the development of new sustainable approaches for efficient REE separation and recovery. Herein, we report on the development of polyethylenimine (PEI) cross-linked cellulose nanocrystal (CNC) materials for use as high performance sustainable adsorbents for REEs. This cross-linking reaction occurs in aqueous solution and traditional toxic cross-linkers are not involved. Importantly, PEI acts not only as an emerging cross-linker but also as coordination sites for REE binding. The adsorbents were qualitatively and quantitatively characterized by transmission electron microscopy (TEM), Fourier transform infrared (FT-IR) spectroscopy, X-ray photoelectron spectroscopy (XPS), elemental analysis, zeta-potential, thermogravimetric analysis (TGA), and conductometric–potentiometric titration. In a single-component system, the adsorption behavior showed heterogeneous adsorption capacities of 0.611, 0.670, and 0.719 mmol g −1 for La(iii ), Eu(iii ), and Er(iii ), respectively. The similarity of chemical properties makes REEs difficult to separate from each other, but the materials displayed preferential adsorption for Er(iii ) compared to La(iii ) and Eu(iii ) in a ternary REE solution. The FT-IR, XPS and EDS mapping results revealed the importance of the primary and secondary amino functional groups as the principal REE binding sites. Overall, this study demonstrates a facile route for separation, recovery, and enrichment of REEs from aqueous solution.